In silico Molecular Docking Analysis of Stephania glabra phytocompounds Targeting Thymidylate Kinase for potential Antituberculosis Activity - Sandeep Chandaragi (International Journal of Molecular Biotechnological Research, 2025)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis. It mainly affects the lungs and spreads through the air when a person with active TB in their lungs coughs, sneezes, or spits. This study investigates several bioactive compounds derived from plants to forecast how effective plant-based ligands will be at preventing tuberculosis. The purpose of the study was to use computational techniques to assess the effectiveness of several phytochemicals against the Mycobacterium. Molecular docking was systematically carried out using the virtual screening software PyRx. The top 5 phytocompounds from Stephania glabra were chosen among them to test their compatibility with the thymidylate protein 5NR7, using the ADMET filters, the ligands pharmacological evaluation was performed. The phytocompounds Roemerine, Stepholidine, Tetrahydropalmatine, Rotundine, Corydalmine from the plant Stephania glabra were discovered to be the most potent antagonist for the protein Thymidylate kinase. All of the bioactive chemicals could be considered as deserving candidates for the suppression of tuberculosis due to their strong affinity for the protein. Among the top ligand the phytoconstituent Roemerine demonstrated better binding affinity with target.
Keywords: Adenosine triphosphate (ATP); Blood-Brain Barrier (BBB); C-type lectin receptors (CLRs); Gastrointestinal absorption (GI); Molecular Doching (MD); Mycobacterium tuberculosis (Mtb); Nod-like receptors (NLRs); Stephania Glabra; Thymidine -5'triphosphate (dTTP); Thymidine diphosphate (dTDP); Thymidine monophosphate (dTMP); Thymidylate kinase (TMK); Toll-Like receptors (TLRs); tuberculosis (TB)